An effective method for preventing cholestatic liver injury of Aucklandiae Radix and Vladimiriae Radix: Inflammation suppression and regulate the expression of bile acid receptors. (10th August 2022) - Chen, Ziqiang; Wei, Chunlei; Yu, Ziwei; Yang, Ke; Huang, Zecheng; Hu, Huiling; Wang, Zhan-guo
Abstract: Ethnopharmacological relevance: Aucklandiae Radix (AR) and Vladimiriae Radix (VR) were used to treat gastrointestinal, liver and gallbladder diseases at practice. In most conditions, VR was used to be a substitute of AR or a local habit may attribute to the same main active ingredients Costunolide and Dehydrocostus lactone, which presented many similar pharmacological activities. However, other different lactone compounds in AR and VR also play a role in disease treatment, so the difference in therapeutic effects of AR and VR in related diseases needs to be further studied. Aims of the study: Revealing the differences between the chemical compounds of the total lactone extracts of AR and VR (TLE of AR and VR) and the differences in the protective effects of cholestatic liver injury to ensure rational use of AR and VR. Study design and methods: The macroporous adsorption resin was used to purify and enrich the lactone compounds to obtain the total lactone extracts of AR and VR. HPLC-PDA was used to obtain the data to establish chemical fingerprint and chemometric analysis to compare similarities and differences between TLE of AR and VR. The pharmacodynamic experiment revealed how TLE of AR and VR to show protect effects on cholestatic liver injury. Results: Similarity analysis results showed TLE of AR and VR had a high similarity (>0.9). Nevertheless, difference analysis results showed 4 compounds, Costunolide, Dehydrocostus lactone, 3β-acetoxy-11β-guaia-4 (15), 10 (14)-diene-12, 6α-olide and vladinol F may contribute to the differences between them. The pharmacodynamics experiments results showed the TLE of AR and VR affected the different liver cholate-associated transporters mRNA expression (TLE of AR up-regulated CYP7A1, TLE of VR down-regulated FXR and BSEP), the TLE of AR and VR had an effect to regulate biochemical indicators (AST, ALT, ALP, TBA) of liver function, and TLE of VR was better than TLE of AR in reducing the expression of inflammatory factors (IL-6 and IL-1β). Conclusion: The liver protection of AR and VR have been confirmed, but the differences of material basis and mechanism of drug efficacy needed further study to guarantee formulation research and provide theoretical references for clinical rational applications of AR and VR. Graphical abstract: Image 1 Highlights: Using macroporous adsorbent resin to purify and enrich the TLE of AR and VR. Comparing chemical compounds similarities and differences between TLE of AR and VR. Comparing pharmacodynamics similarities and differences between TLE of AR and VR. AR and VR both have liver protection, but the mechanism may be different.